Zhongguo gongchandang shizhong daibiao Zhongguo xianjin wenhuade qianjin fangxiang
'The Chinese Communist Party represents throughout the progressive orientation of the advanced culture in China. ' Printno. 85322.18361-2. Second sheet of the series devoted to the Three Represents (Jiang Zemin Theory). See also BG E15/142-4.